Quality of Care in Family Planning Services: Differences Between Formal and Informal Settlements of Kira Municipality, Uganda - Lukyamuzi, Zubair; Tetui, Moses; Fonseca-Rodríguez, Osvaldo; Atuyambe, Lynn; Makumbi, Fredrick Edward; Baroudi, Mazen (Frontiers in Global Women's Health, 2021)
Background: Family planning (FP) quality of care (QoC) affects contraceptive use and it varies across urban settlement types. This study assesses the difference in service delivery point(SDP) structural and process factors between formal and informal urban settlements, and client’s opinions on the QoC in informal settlements. This is useful in creating an evidence base to advocate for better quality services for the most vulnerable in society. Methods: This was a cross-sectional survey which included SDPs of Kira municipality in Wakiso district, Uganda. Data were collected from all service points in Kira municipality whose caretakers consented. In addition, using multi-stage sampling, 626 women of reproductive age (15 to 49years) who had lived in informal settlements of Kira municipality were interviewed. Data were collected using structured questionnaires, descriptive analysis was carried out in Stata version 14.0, Chi square and t-tests were used to compare informal with formal settlements. Results: Formal settlements generally had more higher level SDPs compared to informal settlements (p-value <0.001). SDPs in formal settlements provided more FP methods and had more community health workers (CHW) to support their work. Also, SDPs in formal settlements were more likely to have long term FP methods available and more likely to have trained personnel to insert and remove implants and IUDs compared to those in informal settlements. Additionally, more SDPs in formal settlements provided counseling for permanent, long term and short term FP methods. Of the 626 interviewed women, most (68.6%) reported that they would not return to the previous FP provider or refer a friend to the same provider (72.7%). Conclusions: There is a lower quality FP services in the informal settlements with a commensurable effect on client satisfaction with the services. Therefore improving the quality of FP services in informal settlements should be a top priority. Improved quality of services could act as a motivation to increase the uptake of modern contraceptives in such settings.